1973
DOI: 10.1172/jci107466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Blood Oxygen Affinity on Work Performance of Rats

Abstract: A B S T R A C T Influence of altered blood oxygen affinity on maximal performance ability was evaluated in trained rats exercising to exhaustion in a graded treadmill test. Modification of blood oxygen affinity was achieved both by 2,3-diphosphoglycerate depletion, accomplished by exposure of animals to C02 and by exchange transfusion with blood exposed to bisulfite or stored in acid citrate dextrose, and by carbamylation of hemoglobin, produced by exchange transfusion of blood incubated with potassium cyanate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Some authors claim that an increased Hb oxygen affinity has a detrimental effect on tissue oxygenation (5-7), whereas others have found that an increased Hb oxygen affinity is of no disadvantage or only a slight disadvantage in this respect (8)(9)(10)(11)(12)(13). One explanation for the varying opinions may be that different organs have been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors claim that an increased Hb oxygen affinity has a detrimental effect on tissue oxygenation (5-7), whereas others have found that an increased Hb oxygen affinity is of no disadvantage or only a slight disadvantage in this respect (8)(9)(10)(11)(12)(13). One explanation for the varying opinions may be that different organs have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental evidence for this, however, is conflicting. Some authors have found a detrimental effect of a leftshifted ODC (5-7), while others have found it to be of either no or only a slight disadvantage (8)(9)(10)(11)(12). In a recent study (13), we measured tissue oxygen pressure in rats with increased hemoglobin oxygen affinity without finding any untoward effects.…”
Section: Introductionmentioning
confidence: 95%
“…The It has been shown that the greater the severity of anemia in humans and rats, the greater the decrement in work capacity (1)(2)(3)(4)(5)(6)(7)(8). Decreased O2 carrying capacity of blood (7) and decreased O2 utilizing capacity of tissues (1, 3, 9-11, 26, 27) decreased maximal capacity of O2 consumption (7).…”
Section: Discussionmentioning
confidence: 99%
“…Valeri and Collins [11], for example, observed no effect on oxygen consumption or cardiac output in eight patients who received up to 2,500 ml of low 2,3-diphosphoglycerate donor blood. Woodson et al [12] found that the work per formance of rats was relatively unaffected by exchange transfusion which resulted in a marked increase in hemoglobin-oxygen affinity. Recently, Riggs et al [9] have reported no change in oxygen consumption or cardiac output in Rhesus monkeys in which oxygen affinity was increased by similar means.…”
Section: Discussionmentioning
confidence: 99%